Evaluasi toksisitas insektisida sintetik terhadap lebah Tetragonula laeviceps Smith: Ancaman bagi penyerbuk di pertanian: Toxicity evaluation of synthetic insecticides on Tetragonula laeviceps Smith: Threats to pollinators in agriculture - Mubin, Nadzirum; Dewanthi, Syifa Aiko; Audia, Bela Hasna (Jurnal Entomologi Indonesia, 2025)
Stingless bees (Tetragonula laeviceps Smith) play a crucial role as pollinators in agricultural ecosystems, but their populations are increasingly threatened by synthetic insecticide uses. This study aimed to evaluate the effects of five insecticides on T. laeviceps through topical, residual, and oral applications, both individually and in combination with the adjuvant Agristik 400 L (AG). The tested insecticides included indoxacarb, chlorfenapyr, indoxacarb + chlorfenapyr, flupyradifurone, and abamectin + acetamiprid. The results showed that all insecticides caused 100% mortality at the recommended concentrations. Flupyradifurone had the lowest LC50 values (0.35 ppm for topical application, 0.73 ppm for residual, and 0.94 ppm for oral), indicating the highest toxicity compared to other insecticides. The addition of adjuvants significantly increased insecticide toxicity, especially in residual and oral applications. Unwise insecticide use poses a serious risk to pollinator populations and agricultural ecosystems. Therefore, insecticide application should consider plant flowering phases to minimize its impact on bees, and sustainable pest management strategies should be promoted to ensure environmental balance and agricultural productivity.